Universal infrared system using Raspberry Pi - Tan, Hung Mheng (2025)
This project focuses on the development of a Universal Infrared System using Raspberry Pi for academic research and practical implementation in smart home environments. The aim is to provide a clear methodology and hardware design framework that demonstrates how a single-board computer can serve as a centralized controller for multiple household appliances. The Raspberry Pi, equipped with GPIO (General Purpose Input/Output) pins, is used to interact with electronic components and explore Internet of Things (IoT) applications. By integrating the open-source Linux Infrared Remote Control (LIRC) software, the Raspberry Pi functions as both an infrared signal receiver and transmitter. In order to receive IR commands from conventional remote controls, an IR receiver module is connected to the GPIO pins, while IR LED transmitters are used to send commands to the target appliances. Infrared codes from various remotes such as those for lights, fans, and humidifiers are captured, recorded, and stored. These codes can then be retrieved and transmitted via the Raspberry Pi, allowing users to control multiple devices through a single, unified platform.